2018
DOI: 10.1002/1873-3468.13262
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed processing of the carbohydrate‐binding module of family 54 significantly impairs its binding to polysaccharides

Abstract: Carbohydrate‐binding modules of the family 54 (CBM54) are characterized by spontaneous rupture of the peptide bond Asn266‐Ser267 (numbering corresponds to that of laminarinase Lic16A of Ruminiclostridium thermocellum). As a result of processing, two parts are formed noncovalently connected to each other. Here, to gain insights into the functional significance of the internal cleavage, we made modifications of the family‐conserved processing site in CBM54 of Lic16A. We demonstrate that the introduced mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Although the mechanism of the spontaneous cleavage of VxAly7B is still unclear, we found that the reaction was slow and the increase in temperature and the extension of time will accelerate its progress (Figure 1D and Supplementary Figure 4). The internal cleavage of CBM54 of laminarinase Lic16A and chitinase ChiW is a common feature, and the spontaneous cleavage of CBM54 is essential for the combination of the catalytic module and insoluble polysaccharides (Itoh et al, 2014;Dvortsov et al, 2018). The N-terminal extension (CBM_4_9 module) of AlyA and aly-SJ02 helps the protein to be folded correctly and then breaks, which is a common phenomenon of PL18 family alginate lyases (Matsushima et al, 2010;Dong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of the spontaneous cleavage of VxAly7B is still unclear, we found that the reaction was slow and the increase in temperature and the extension of time will accelerate its progress (Figure 1D and Supplementary Figure 4). The internal cleavage of CBM54 of laminarinase Lic16A and chitinase ChiW is a common feature, and the spontaneous cleavage of CBM54 is essential for the combination of the catalytic module and insoluble polysaccharides (Itoh et al, 2014;Dvortsov et al, 2018). The N-terminal extension (CBM_4_9 module) of AlyA and aly-SJ02 helps the protein to be folded correctly and then breaks, which is a common phenomenon of PL18 family alginate lyases (Matsushima et al, 2010;Dong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%